(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
An analysis of 121 medical histories of children with obesity aged 5 to 17 years was conducted. The leading complications and concomitant diseases are: gastropathology (96%), cardiac disorders (50%), metabolic disorders (47%), hypothalamic syndrome (46%), accelerated or accelerated physical development (85%), delayed sexual development in boys (25%), accelerated puberty (60%) and hyperandrogenism in girls (5%). It was found that metabolic syndrome was 1.5 times more common in children with 1-2 degrees of obesity than in children with 3rd degree of obesity. A high incidence of morbidity in children with obesity was revealed, which reflects reduced immunological reactivity of the body.